PENGARUH BRAND TRUST DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SEPEDA MOTOR HONDA BEAT DI KECAMATAN KARANGPILANG, KOTA SURABAYA - pratama, ferdian adi; dwiarta, i made bagus (Universitas PGRI Adi Buana, 2017)
The research aims to know the purchasing decisions of consumers in order to increase product sales Honda Beat motorcycle in Karangpilang subdistrict of Surabaya. Some of the variabels analyzed as factors that affect the purchasing decision is Brand Trust and Product Quality. The population is the entire Honda Beat motorcycle user in Karangpilang Subdistrict of Surabaya and the samples that are 189 respondents. Sampling technique used was Accidental Sampling. The data collected with a questionnaire and analyzed using Multiple Linier Regression Analysis, hypotheses using F test and T test. The results shows that Brand Trust and Product Quality simultaneously and partially are significant influences toward purchase decision. Based on the data analysis that concluded that there was a simultaneous influence between Brand Trust and Product Quality of Purchase with a value of F of 8,603 sign at 0,000. While testing partially showed that each variable effect on competence with a value of tcalculate Brand Trust of 2,950 sign of 0,000 and Product Quality of 2,619 sign at 0,010. Key words : brand trust, product quality, purchase decision